Hubungan Masa Kerja Dengan Kejadian Gangguan Pendengaran Pada Karyawan PT. Riau Graindo Pekanbaru Tahun 2019 - Retno Putri; ‘Izzatu Fatkhur Rahman; Sri Marhaeni (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
Background: Hearing loss is one of the occupational diseases. A noisy work environment as one of the impacts of the industrial sector. This is the most common cause of hearing loss. The National Institute of Health in 2012 reports that about 15% of Americans aged 20-69 years experience hearing loss in connection with work activities, because noise can cause hearing loss, the government sets standards that regulate permissible noise exposure. Hearing loss due to noise occurs slowly, in a matter of months to years. This is often not realized by the sufferer, so that when the patient starts complaining of hearing loss, it is usually already in an irreversible stage. Such conditions will affect labor productivity which will ultimately cause a decrease in the health of the workforce. In certain cases, hearing loss due to noise begins for 6 to 10 years after exposure to loud noises. PT. Riau Graindo was established on January 17, 1997 located in Desa Sidomulyo Barat Kecamatan Tampan Kota Pekanbaru, a publishing company under of Riau Pos Group (RPG), based in Pekanbaru. Research Objectives: To determine corelations of work period with the incidence of hearing loss in employees of PT. Riau Graindo Pekanbaru in 2019. Research Methods: This study was an observational analytic study with a cross sectional approach. Research Results: Majority of PT. Pekanbaru Graindo Pekanbaru that is > 5 years as many as 21 people (70%). The majority of employees of PT. Riau Graindo Pekanbaru experiencing hearing loss as many as 18 people (60%). Chi square test results obtained Pvalue = 0.001, it can be concluded that there is a relationship between work period and the incidence of hearing loss in the employees of PT. Riau Graindo Pekanbaru in 2019. Conclusion: It can be concluded that there is a relationship between working period and the incidence of hearing loss in the employees of PT. Riau Graindo Pekanbaru in 2019 with Pvalue = 0.001 smaller than α (0.05).